Comparison of Warm Sitz Bath and Ice Therapy for Postoperative Management After Hemorrhoidectomy - Hoogar, Prafullachandra; Kumar K H, Praveen; Kanakapur, Sachin; R Navalyal, Sanjeev (Journal of Neonatal Surgery, 2025)
Background: Hemorrhoidectomy is a common surgical procedure for grade 3 and 4 hemorrhoids, often associated with significant postoperative pain and wound healing challenges. This study aimed to compare the efficacy of warm sitz bath and ice therapy in postoperative pain management and wound healing after hemorrhoidectomy. Methods: A prospective comparative study was conducted at KLE Co-operative Hospital and affiliated KAHER institutes in Hubballi, North Karnataka. One hundred twenty patients (60 in each group) aged 18-75 years with grade 3 or 4 external hemorrhoids undergoing Ferguson's hemorrhoidectomy were randomized to receive either warm sitz bath or ice therapy postoperatively. Pain was assessed using the Visual Analog Scale (VAS), and wound healing was evaluated using the REEDA scale (Redness, Edema, Ecchymosis, Discharge, Approximation) at 24 hours, 3 days, 7 days, and 14 days postoperatively. Secondary outcomes included analgesic consumption, patient satisfaction, and time to return to normal activities. Results: Patients in the ice therapy group experienced significantly lower pain scores at 24 hours (mean VAS: 5.2±1.3 vs. 6.8±1.5, p<0.001) and 3 days (mean VAS: 3.8±1.1 vs. 4.9±1.3, p<0.001) compared to the sitz bath group. However, the sitz bath group demonstrated better wound healing parameters at 7 days (mean REEDA score: 3.1±0.9 vs. 4.2±1.1, p<0.001) and 14 days (mean REEDA score: 1.2±0.6 vs. 2.3±0.8, p<0.001). Analgesic consumption was significantly lower in the ice therapy group during the first 3 days (p=0.002), while patient satisfaction scores were comparable between groups at the end of the follow-up period (p=0.346). Conclusion: Ice therapy provides superior early postoperative pain control and reduces analgesic requirements following hemorrhoidectomy, while warm sitz bath promotes better wound healing in the later recovery phase. A sequential approach of ice therapy in the immediate postoperative period followed by warm sitz bath after 3-4 days may optimize both pain management and wound healing outcomes